Promoting environmentally sustainable occupational engagement on a college campus: a case study. Issue 1 (2nd January 2020) - Lucas Molitor, Whitney; Kielman, Konner; Cooper, Jay; Wheat, Kendel; Benson, Alison
ABSTRACT: Despite a growing body of literature supporting the role of occupational therapy in promoting environmentally sustainable lifestyles, few published articles provide a sound rationale for use of this evidence in occupational therapy practice. As such, the purpose of this article is to demonstrate how occupational therapists can transfer evidence-based skills from similar areas of practice to promote environmentally conscious habits and develop a social support network to maintain these skills. In this case illustration, we will use Ray's story to demonstrate how occupational therapy intervention can be used to modify occupational behaviour for a positive impact on the environment.